2019
DOI: 10.1002/pen.25195
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the rheological and reinforcing effects of graphene oxide on glassy and semicrystalline polymers

Abstract: In this work, a comparative study was performed on nanocomposites, based on three different polymeric matrices, namely polylactic-acid (PLA), polystyrene (PS), and linear lowdensity polyethyelene (mLLDPE), produced by metallocene catalyst. The reinforcing agent was graphene oxide (GO) at one percentage content (1 wt%) and the nanocomposites were prepared by the melt-mixing procedure, whereas the matrix type employed was found to be decisive in the thermomechanical properties improvement. The thermomechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…A laser extensometer—type cross‐scanner by Fiedler Optoelektronik GmbH, was used for the strain evaluation. The experimental procedure is presented in detail in [34].…”
Section: Methodsmentioning
confidence: 99%
“…A laser extensometer—type cross‐scanner by Fiedler Optoelektronik GmbH, was used for the strain evaluation. The experimental procedure is presented in detail in [34].…”
Section: Methodsmentioning
confidence: 99%
“…Even at high loading levels, the addition of graphene decreased the creep displacement by 20.5%. Charitos et al [ 161 ] also reported increased creep resistance of PLA/GO (1 wt%) in comparison with the neat polymer. Similarly, Ramazani et al [ 162 ] also reported an increase in creep resistance of 24% and 41% for PCL/GO and PCL/reduced GO composites (0.1 wt%), respectively.…”
Section: The Potential Of Novel Graphene–polymer Composites For Tendomentioning
confidence: 98%
“…[2,8] Although graphene has these desirable properties, largescale fabrication of the monolayer structure is difficult and costly. Various graphene derivatives have been used to reinforce the polymers such as graphene oxide (GO), [9,10] reduced graphene oxide (rGO), [11] expanded graphite, and GNP. [8,12] However, especially the high costs of GO and rGO and the harsh chemicals used in their production limit their industrial applications.…”
Section: Introductionmentioning
confidence: 99%